The Federated Event Service - Ryan, Conor (Trinity College Dublin. Department of Computer Science, 2003)
Event services provide asynchronous, decoupled, anonymous message-based communication. This facilitates scalable distributed systems composed of autonomous concurrently executing entities. There are several kinds of event services in existence addressing wide ranging issues such as Internet scale, quality of service, mobility and location awareness. When integrating systems that use disparate event services it may be necessary to inter-work their event services to facilitate communication between the systems. A federated service is a collection of autonomous concurrent services that may be linked together to provide a single logical service. There is currently no standard solution available for heterogeneous event service inter-working. In the absence of a standard solution, system developers are forced to roll their own solutions. This is problematic as such solutions can cost time, money and effort. These solutions may be sub-optimal since developers, unless they are experts in event systems and event system inter-working, may not have considered or understood all of the issues involved. Primarily, this project examines the thesis that a standard mechanism for federating heterogeneous event services is a valuable solution for addressing this event-service inter-working problem. A secondary aim of the project is to investigate whether such a mechanism is a viable alternative to bespoke solutions for building or extending event-based systems, when requirements cannot be met by a single event service. To this end, the design, implementation and evaluation of such a mechanism, called the Federated Event Service (FES), was carried out. A test application that federates three different kinds of event services was also built. It was determined that the FES approach is an adequate and cost effective solution for many inter-working requirements, but federation in general cannot address end-to-end event context integrity.
Keywords: Computer Science